Managing sustainability: the role of multinational corporations in the global south - Jacquinet, M.; Bussotti, L. (Problems of Management in the 21st Century, 2019)
Multinational corporations and international business practices as well as international investment are considered important elements for the diffusion of new modes of production, namely through a flow of cleaner production and new management practices such as corporate social responsibility (CSR). This view is lacking consistency and is not buttressed on strong empirical evidence. The positive driver of environmental sustainability is probably not international business and trade but strong and good institutions. The focus here is on four limitations: the context of the private firms and corporations, the workings of complex organizations, the technology and the right institutions that buttress the global, national and local contexts, taking as concrete examples some specific cases from the Global South, as Mozambique. The article concludes that these aspects have to be considered and contrasted to the technological and management solutions for sustainability.